Stability of rigid retaining wall [compact disc] - 302663 Lee, Phoi Yean (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2004